The Democracy to Come? An Enquiry Into the Vision of Blockchain-Powered E-Voting Start-Ups - Imperial, Miranda (Frontiers in Blockchain, 2021)
This research set out to analyze blockchain’s applications for the purpose of e-voting (Blockchain-Powered E-voting, BPE) and the perceived effects of this technological solution on democratic outcomes. Employing Norman Fairclough’s Critical Discourse Analysis (CDA), I examined the written output of seven BPE start-ups (Agora, DemocracyEarth, Follow My Vote, Polys, Voatz, Votem, and VoteWatcher), as displayed in their websites. The close attention of CDA to power relations brought out relevant topics of discussion for analysis. Notably, these included: voting as an expression of democracy; technological determinism; individual versus communitarian understandings of democracy; the prominence of neoliberalism and the economic sphere; and technological literacy. Findings from the literature suggest that the assumptions of BPE start-ups about a blockchain-powered democracy diverge from widely accepted understandings of democracy. BPE start-ups envision a democracy determined by positions and institutions of power, by the technologically able, and by economic interests. This research argues that this conception of democracy disempowers voters from any form of decision-making regarding how democracy is run beyond their expression in the form of a vote decided by these established powers. The widespread addresses to existing elites to enable BPE, as well as what is left unsaid about community, collective rights and the not so technologically literate population, imply that BPE developers display concern for one particular expression among the many diverse and heterogeneous understandings of democracy. This work is a contribution to much needed research on technology and democracy’s deepening intersections, at a time of rapid technological innovation and turbulent democratic skepticism.